Moral order as necessity and as impossibility : common sense, race and the difficulty of change among four 'poor white' families in Newcastle - Peens, Michelle (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA (Sociology and Social Anthropology))--University of Stellenbosch, 2011.